2023
DOI: 10.3390/diagnostics13071303
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics, a Promising New Discipline: Example of Hepatocellular Carcinoma

Abstract: Radiomics is a discipline that involves studying medical images through their digital data. Using “artificial intelligence” algorithms, radiomics utilizes quantitative and high-throughput analysis of an image’s textural richness to obtain relevant information for clinicians, from diagnosis assistance to therapeutic guidance. Exploitation of these data could allow for a more detailed characterization of each phenotype, for each patient, making radiomics a new biomarker of interest, highly promising in the era o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 8 , 9 Radiomics-based techniques have a number of benefits, including the fact that they are noninvasive and the features can be derived from routine medical images. 10 , 11 These make them ideal for translating to clinical practice as the method does not involve invasive procedures to predict or monitor a patient's response to various therapeutic interventions. Studies in the literature have found that radiomics can be used to build diagnostic or predictive biomarkers in a variety of malignancies, including advanced solid tumors, melanoma, and other types of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Radiomics-based techniques have a number of benefits, including the fact that they are noninvasive and the features can be derived from routine medical images. 10 , 11 These make them ideal for translating to clinical practice as the method does not involve invasive procedures to predict or monitor a patient's response to various therapeutic interventions. Studies in the literature have found that radiomics can be used to build diagnostic or predictive biomarkers in a variety of malignancies, including advanced solid tumors, melanoma, and other types of NSCLC.…”
Section: Introductionmentioning
confidence: 99%